Planar Array Antenna with Radiation Pattern Reconfigurability Using PIN Diode - Gamawati Erta Lestari, Sitia
Modern data communication, such as wireless technology with IEEE 802.11 b/g/n standard, requires the antenna with the ability to conform to the changing environment. In this research, antenna capable of being reconfigured to adjust of the changing environments is proposed. The antenna is printed on two layers of circular FR4 Epoxy dielectric substrate (relative permittivity of 4.2, tangent loss of 0.02, thickness of each of 1.6 mm). On top side of the first layer, eight square patches workable at the frequency of 2.4 GHz are fed using a microstrip feeding line based on proximity coupling technique. The size of each patch is 30×30 mm2. The angular distance between adjacent patches is 45°. The microstrip feeding line is printed on top side of the second layer, while the groundplane (diameter 270 mm) is placed on the reverse side. PIN diodes (SMP1345-079LF) are implemented at the end of microstrip feeding line arms to modify the radiation pattern behaving like a switch that connects or disconnects the feeding line to the groundplane. Chip capacitors (100 pF) are placed between PIN diodes and microwave source to block the direct current (DC) travelling to the microwave source. Meanwhile, chip inductors (33 ?H) are placed between PIN diodes and DC source to prevent alternating current (AC) moving to the DC source. When two antennas, positioned across from each other, are set to active, measured reflection coefficient is -14.39 dB at the frequency of 2.4 GHz. The measured antenna has -10 dB working bandwidth of 240 MHz from 2.32 GHz to 2,56 GHz and gain of 0.25 dBi.